Designing the Curriculum of the Islamic Banking Study Program towards Higher Education Sustainable Learning - Purnama Putra; Rizal Fahlevi; Rafika Rahmawati; Isfandayani Isfandayani (AL-ISHLAH: Jurnal Pendidikan, 2024)
The acceleration of change with the COVID-19 pandemic has made a leap in all aspects, including the banking industry. Islamic banking, which is only a few decades old, has shown a significant increase in assets and institutions that need to be supported by the presence of human resources who understand the characteristics of these institutions so that they do not only focus on domestic affairs but develop overseas. Redesigning the Islamic banking curriculum is urgent in order to prepare the students to become graduates who can be in line with the needs of industrial world. This study aims to redesign the Islamic banking curriculum through in-depth study of stakeholders, namely study program administrators, industry associations (Islamic banking), graduate users, and scientific associations. The method used in this research is a combination by first mapping using the Strength, Weakness, Opportunity and Threat (SWOT) method and then deepening and matching it with the Analytic Network Process (ANP) method to produce priority strategy. The priorities generated based on the SWOT and ANP matrices are : (1) Increasing stakeholder links and matches, (2) Increasing graduate competence, (3) Periodic review and evaluation of the curriculum, (4) Increasing Lecturer capacity. Therefore, Sustainable learning in Islamic banking must be supported by stakeholders by linking and matching in order to fill the need with the availability of competent human resources.